Diagnosis of Bernard-Soulier syndrome and Glanzmann's thrombasthenia with a monoclonal assay on whole blood. - Montgomery, R R (1983)
Two hereditary platelet disorders, Bernard-Soulier syndrome and Glanzmann's thrombasthenia, are characterized by selective deficiencies of platelet membrane glycoproteins. Murine monoclonal antibodies were developed against platelet membrane glycoprotein Ib and against the glycoprotein IIb/IIIa complex. A rapid whole blood assay for the deficiency of these glycoproteins was developed and used to study whole blood samples from six patients with Glanzmann's thrombasthenia and three patients with Bernard-Soulier syndrome. Patients with type I and type II Glanzmann's thrombasthenia were easily detectable with this assay. This permits the diagnosis of these disorders on 200 microliters of whole blood within 2 h of blood sampling.